2023
DOI: 10.1590/2317-1545v45273211
|View full text |Cite
|
Sign up to set email alerts
|

Lignin monomeric composition in soybean seed coats and resistance to mechanical damage

Thaís Valério Raimundo Menino,
Breno Miguel Joia,
Aline Marengoni Almeida
et al.

Abstract: Soybean seeds are crucial for global food production. Various factors affect the quality of soybean seeds, including mechanical damage, which can lead to reduced germination potential and decreased seedling vigor. The presence of lignin in the seed coat contributes to resistance to mechanical damage. However, the relationship between the monomeric composition of lignin and mechanical damage is unknown. To fill this gap, we evaluated the contents of monomers hydroxyphenyl (H), guaiacyl (G), and syringyl (S) in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…According to Souza and Marcos-Filho [7], seed longevity correlates with the seed tegument permeability, and the lignin level in the seed tegument correlates with the seed's mechanical resistance. Capeleti et al [29] and Menino et al [30] also concluded that the seed coat lignin content and composition correlate positively with the resistance of soybean seeds to mechanical damage.…”
Section: Seed Coat Crackingmentioning
confidence: 97%
“…According to Souza and Marcos-Filho [7], seed longevity correlates with the seed tegument permeability, and the lignin level in the seed tegument correlates with the seed's mechanical resistance. Capeleti et al [29] and Menino et al [30] also concluded that the seed coat lignin content and composition correlate positively with the resistance of soybean seeds to mechanical damage.…”
Section: Seed Coat Crackingmentioning
confidence: 97%
“…PAL is an important enzyme involved in a plant's reaction to a wound and functions as a catalyst in the phenylpropanoid pathway [6]. After the synthesis of trans-cinnamic acid, different catalytic reactions lead to the generation of different phenolic compounds, such as sinapic acid, ferulic acid, caffeic acid, and p-coumarate, which are converted into their respective monomers (sinapyl, coniferyl, feruloyl, and p-coumaryl alcohols) by esterification, methoxylation, hydroxylation, and reduction reactions [17]. These monolignols are then further polymerized by peroxidase enzyme (POD) into lignin and suberin [18].…”
Section: Woundingmentioning
confidence: 99%